Usages Et Vulnerabilite De Pterocarpus Santalinoides L’her. Ex De (Papillionoidae), Une Plante Utilisee Dans Le Traitement Des Gastro-Enterites Dans Le Sud Du Benin - A C., Ayena; Tchibozo M., Agassounon Djikpo; A. E., Assogbadjo; H., Adoukonou-Sagbadja; G. A., Mensah; C., Agbangla; C., Ahanhanzo (European Scientific Journal, ESJ, 2016)
In West Africa, rural populations depend heavily on woody plant resources to satisfy particular nutritional and therapeutic needs. This study was conducted in South of Benin to identify local knowledge about Pterocarpus santalinoides, and its vulnerability level. Investigations were made using an interview guide followed by observations. 180 professionals were interviewed. It appears from the study that the "African teak" is known as 10 local designations. The species is sought in many areas of use (African medicine, food medicine, carpentry, art, energy and well-being). On medicinal plan, leaves, bark of the trunk and roots are solicited alone or in association with others to treat especially the symptoms related to gastroenteric (diarrhoea, dysentery, vomiting and abdominal cramps). Decoct is the main galenic form adopted for the treatment of these conditions. Considering all the sectors, all its vegetative organs are used. Degree of uses of various organs of this plant is the main causes of its vulnerability. Vulnerability index (Iv) is equal to 2.4. The species is thus identified as vulnerable. It is urgent for its users to adopt a sustainable management approach, in order to preserve African teak.